Data-Driven Predictive Analysis of COVID -19 Outbreaks in China and India - Pallavi Ranjan (International Journal of Advanced Science and Technology, 2020)
Coronavirus pandemic that is currently spreading at an alarming speed rate and triggered as global health emergency by World Health Organization. The epicenter of this virus is Wuhan located in the Hubei province of China having exponentially high cases at the early start, is currently having controlled situation by seeing a dramatic decrease in the number of cases with almost negligible death rate. However, India overtakes China and currently the eleventh most coronavirus affected countries in the world. This paper provides comparative analysis of the global outbreak of coronavirus using the situational summary timelines for both the countries. Use of predictive analytics is done to forecast and compare the outbreak pattern in the two largest and densely populated Asian countries. Time series coronavirus data set is obtained from John Hopkins University and forecasting approach using expert modeler is used for building the prediction model using IBM SPSS statistics tool. This paper helps to study the pattern for both countries and specifically measures that can be taken by India to reduce the cases as India opens lockdown due to starving economy and stands at a high risk infection due to the thickness of population